Cooperative behavior between companies and contract farmers in Chinese agricultural supply chains: Relational antecedents and consequences. Issue 5 (11th June 2018) - Fu, Shaoling; Li, Zhiwei; Wang, Bill; Han, Zhaojun; Huo, Baofeng
Abstract : Purpose: The purpose of this paper is to explore the relationships between relationship commitment, cooperative behavior and alliance performance in agricultural supply chains. By investigating dyadic relationships between companies and their contract farmers (hereafter denoted by C+F), this study aims to investigate how relationship commitment influences cooperative behavior and how such behavior further influences alliance performance in C+F agricultural supply chains in China. Design/methodology/approach: Based on data collected from 202 companies and 462 farmers in China, this study uses the structural equation modeling approach to test the conceptual model and related hypotheses. Findings: For both companies and contract farmers, normative relationship commitment is a necessity for economically and socially cooperative behavior (i.e. specific investment and communication, respectively), while instrumental relationship commitment has no relationship with specific investment. Only socially cooperative behavior (communication) can improve alliance performance, while economically cooperative behavior (specific investment) has no relationship with alliance performance. For companies, instrumental relationship commitment reduces communication, but specific investment increases communication. For farmers, both instrumental relationship commitment and specific investment have no relationship with communication. Originality/value: This study contributes to the literature on supply chain management by adopting a bilateral perspective and examining relationships among relationship commitment, cooperative behavior and alliance performance in the C+F context. It provides agricultural companies and contract farmers with valuable guidance to use relationship commitment and cooperative behavior to improve alliance performance in agricultural supply chains in China.